Evolution classical philosophy meets quantum science - Bhattacharyya, Somnath 1976- (CRC Press, 2024)
This book reconceptualizes the ancient philosophy of 'dualism' and a 'trinity' applied to classical and quantum nonequilibrium phenomena. In addition to classical mechanics and electrodynamics, a remarkable connection of this philosophy with quantum mechanics is established, which can be useful for quantum computing and the development of quantum artificial intelligence. Packed with the recent theoretical models, quantum simulations of black holes, and experimental observations of quantum phase transitions, this book brings a holistic approach that can be useful to refine the concept of the 'Creation', i.e., the evolution of the Universe from the condensed state of matter, and explain the artificial vision. The approch is:- Unique: Connects ancient philosophy, classical and quantum mechanics, materials, and the latest quantum technologies- Novelty: High level of scientific interpretation of ancient philosophy, creation, interactions, and disorder- Multidisciplinary: Guides students to learn quantum simulations and develop philosophical ideasThe book contains over ten years of in-depth research by the author on the ancient eastern (Indian) philosophy and the latest scientific research in condensed matter and quantum technology. This book will simplify the picture of ancient eastern philosophy, which can be read by the general audience, particularly undergraduate/postgraduate students interested in quantum information science without any mathematical treatment. However, some parts of the book will be ideal for senior academicians and professional researchers in both worlds